Psychosocial Experiences of Indonesian Performing Musicians In Building a Sustainable Career - Djuanto, Aurelia S.; Y. S. Suyasa, P. Tommy (Pelopor Publikasi Akademika, 2023)
This study explores the challenges and strategies of Indonesian musicians in establishing sustainable careers from psychosocial experiences. The study utilizes Interpretative Phenomenological Analysis (IPA) on six professional musicians with over ten years of experience. The findings reveal the importance of adaptation, personal growth, maintaining passion, and creativity. The study concludes that happiness, health, and productivity are crucial for career sustainability, emphasizing the interrelation of personal identity, social support, and career dynamics in the music industry. The research highlights the need for musicians to navigate psychosocial challenges effectively to build long-term, fulfilling careers.